Revue de presse club des jeunes néphrologues (CJN) : 2e trimestre 2020 de la Dialyse à Domicile - Antoine Lanot; Frédéric Lavainne; Julie Morinière Beaume; Céline Nodimar; Guillaume Seret; Laurence Vrigneaud; Stanislas Bataille; Odette Carceles; Morgane Gosselin (Bulletin de la Dialyse à Domicile, 2020)
Introduction (NDLR)